Relevansi Kepemimpinan Misi Dalam Pemberdayaan Jemaat Umur 15-20 Tahun - Yulian Anouw (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2023)
Abstract,Relevance of Mission Leadership is one part of Christian activity. The description above states some ideas about the relevance of Mission Leadership, specifically in the Meree tribe as follows; First, the relevance of Mission Leadership in the Meree tribe has the essence of Mission can be learned and applied; Second, Mission Leadership in the Meree tribe in having Evangelical content/materials; Third; Mission Leadership in the Meree tribal community is carried out with the aim of winning the Meree tribal community qualitatively. The ideas as stated above indicate the importance of understanding the nature, Mission Leadership and Mission goals in the Meree tribal community. This is considered important because this understanding has an important role in the context of local culture in society, which has an impact on achieving the goals of Mission Leadership in society, namely quantitative community development